1998
DOI: 10.1111/j.1349-7006.1998.tb00529.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐cachectic Effect of FK317, a Novel Anti‐cancer Agent, in Colon26 and LX‐1 Models in Mice

Abstract: The effects of FK317 (11-acetyl-8-carbamoyloxymethyl-4-formyl-6-methoxy-14-oxa-1,11-diazatetracyclo[7.4.1.0 2, 7 .0 10, 2 ]tetradeca-2,4,6-trien-9-yl acetate), a novel anti-cancer agent, on murine adenocarcinoma colon26-and human lung carcinoma LX-1-induced cachexia were investigated in mice. Mice bearing colon26 or LX-1 s.c. lost weight and became cachectic, associated with tumor growth. FK317 and mitomycin C (MMC) inhibited the growth of both tumors. FK317 ameliorated the weight loss induced by the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…However, our findings suggest that hochuekkito did not affect adipose triglyceride lipase activity because hochuekkito increased both the serum triglyceride level and fat deposition in cachectic mice but not in healthy controls. Several studies have reported that both the serum triglyceride level and weight of fat tissue were decreased in the terminal stage of cancer cachexia in mice [28, 29]. In this study, we evaluated the effect of hochuekkito on the cachectic state of tumor-bearing mice in the terminal stage, not in the initial stage.…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings suggest that hochuekkito did not affect adipose triglyceride lipase activity because hochuekkito increased both the serum triglyceride level and fat deposition in cachectic mice but not in healthy controls. Several studies have reported that both the serum triglyceride level and weight of fat tissue were decreased in the terminal stage of cancer cachexia in mice [28, 29]. In this study, we evaluated the effect of hochuekkito on the cachectic state of tumor-bearing mice in the terminal stage, not in the initial stage.…”
Section: Discussionmentioning
confidence: 99%
“…25). Naoe et al (26) showed that a significant decrease in the circulating levels of triglyceride was found in the salinetreated tumor-bearing mice compared with the saline-treated normal mice. In the present study, DHMEQ significantly inhibited the decrease of epididymal fat weight and serum triglycerides, presumably through the suppression of IL-6 production.…”
Section: Discussionmentioning
confidence: 99%
“…3), although, in the LX‐1 models, body weight could not be evaluated due to cachexia at the later stage of treatment. ( 23,24 )…”
Section: Resultsmentioning
confidence: 99%
“…3), although, in the LX-1 models, body weight could not be evaluated due to cachexia at the later stage of treatment. (23,24) Effect of trastuzumab, tegafur/uracil or gefitinib in combination with amrubicin in human cancer xenograft models. Next, we examined the effects of trastuzumab, tegafur/uracil or gefitinib combined with amrubicin in vivo using human tumor xenograft models.…”
Section: Effect Of Chemotherapeutic Agents In Combination With Amrubicinmentioning
confidence: 99%